Internalizing the carbon footprint in rice cultivation through solar irrigation - an economic study in Villupuram district of Tamil Nadu, India: Carbon footprint in rice cultivation through solar irrigation - V, NANDHINI; R. VENKATARAMAN,; V BANUMATHY , (ORYZA-An International Journal of Rice, 2024)
This study attempts to highlight the comparative economic and environmental advantages of solar powered irrigation in terms of cost, energy and carbon footprint over the existing electric operated pumping system in rice cultivation. Multi-stage and snowball sampling methods were used in this study. This study was conducted in Villupuram district of Tamil Nadu purposively, as the district has the largest number of energized pumps adopted for irrigation in the state and it will be considered as a second stage. The total sample size of 90 was allotted with a quota of 45 each under electric operated well (EOW) and solar operated well (SOW) category. The cost of irrigation water, energy and carbon footprints were indirectly assessed in this study using some imputation procedures. The hours of irrigation were higher in the case of solar due to lesser horse powered motors and energy rationing is not the binding constraint in SOW unlike EOW. The per liter cost of water output was higher in the case of electric with subsidy and same was higher in the case of solar in without subsidy scenario comparisons. The hours of pumping and imputed energy consumption were higher for rice in the case of SOW compared to EOW. The energy consumption per ha decreased with increasing HPs both in the case of SOW and EOW due to economies of scale operation. The inclusion of social carbon cost in the economic analysis showed that the net income in SOW was higher without any compromise in rice production. In with social carbon cost / benefit scenario, the irrigation cost share was lesser in SOW compared to EOW. Hence it was construed that the SOW internalize the carbon footprints and serve as an important mitigating tool in confronting upcoming climate change risks. The policy makers must pay attention in promoting the subsidized SOW in agriculture, considering the negative and positive externalities involved in these two sources of irrigation.